- #1

- 233

- 1

## Homework Statement

Solve (e^(x^2))` , use this result to solve §5x*e^(x^2)dx

## Homework Equations

* is multiply

` is derive

1.§e^xdx=e^x+C

2.§e^kxdx=1/k*e^kx+C

3.§a^xdx=1/ina*a^x+C (a is a number)

4.§k*f(x)dx=k*§f(x)dx

## The Attempt at a Solution

(I'm alittle confused as to how you 'use' the previous one to solve the next.

The previous example simply states this when solving: [in((x^2)+4)]`

[in((x^2)+4)]`= (in u)`= (1/u)*u`= 1/((x^2)+4)*2x=(2x)/((x^2)+4)

Then you're going to use this to solve §(3x)/((x^2)+4)dx

gives: §(3x)/((x^2)+4)dx = 3/2§(2x)/((x^2)+4)dx= 3/2*in((x^2)+4)+C.

It's not written, so I suppose they are using it by simply putting 3/2 on the outside, using rule 4)

So my try went:

(e^(x^2))`=(e`u)`*u`(um, using the corerule as it is named in norwegian) = e^(x^2)*2x

, which was correct.

Then you use it..

§5x*e^(x^2)dx=(ADSFSDF PRESSING SHIFT FOR A LONG TIME CAN*T WRITE LOL F:: WINDOWS LOL)